Exposure to Kynurenic Acid during Adolescence Increases Sign-Tracking and Impairs Long-Term Potentiation in Adulthood - DeAngeli, Nicole E.; Todd, Travis P.; Chang, Stephen E.; Yeh, Hermes H.; Yeh, Pamela W.; Bucci, David J. (Frontiers in Behavioral Neuroscience, 2015)
Changes in brain reward systems are thought to contribute significantly to the cognitive and behavioral impairments of schizophrenia, as well as the propensity to develop co-occurring substance abuse disorders. Presently there are few treatments for persons with a dual-diagnosis and little is known about the neural substrates that underlie co-occurring schizophrenia and substance abuse. One goal of the present study was to determine if a change in the concentration of kynurenic acid (KYNA), a tryptophan metabolite that is increased in the brains of people with schizophrenia, affects reward-related behavior. KYNA is an endogenous antagonist of NMDA glutamate receptors and α7 nicotinic acetylcholine receptors, both of which are critically involved in neurodevelopment, plasticity, and behavior. In Experiment 1, rats were treated throughout adolescence with l-kynurenine (L-KYN), the precursor of KYNA. As adults, the rats were tested drug-free in an autoshaping procedure in which a lever was paired with food. Rats treated with L-KYN during adolescence exhibited increased sign-tracking behavior (lever pressing) when they were tested as adults. Sign-tracking is thought to reflect the lever acquiring incentive salience (motivational value) as a result of its pairing with reward. Thus, KYNA exposure may increase the incentive salience of cues associated with reward, perhaps contributing to an increase in sensitivity to drug-related cues in persons with schizophrenia. In Experiment 2, we tested the effects of exposure to KYNA during adolescence on hippocampal long-term potentiation (LTP). Rats treated with L-KYN exhibited no LTP after a burst of high frequency stimulation that was sufficient to produce robust LTP in vehicle-treated rats. This finding represents the first demonstrated consequence of elevated KYNA concentration during development and provides insight into the basis for cognitive and behavioral deficits that result from exposure to KYNA during adolescence.